Antimicrobial Materials with Medical Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of the International Journal of Molecular Science comprises a comprehensive study on “Antimicrobial Materials with Medical Applications”. The Special Issue has been inspired by the great progress made in the development of new antimicrobial materials that go beyond the resistance of microbes to modern antibiotics. It covers a selection of recent research and review articles in the field of antimicrobial materials and their medical applications. Moreover, it also provides an overview of this increasingly diverse field, presenting recent developments and the latest research, with particular emphasis on new antimicrobial surfaces, medical devices, contact lens, package materials, etc.